Application of Zakat, Infak / Alms accounting based On PSAK 109 - Febryandhie Ananda; Nugroho Noto Diharjo; Josua Sahala (Universitas Kristen Indonesia Toraja, 2022)
Study this aim for knowing application zakat, infaq / alms accounting based on PSAK 109 at the national amil zakat institution Yakesma Medan. Type research used _ is qualitative . subject study is national amil zakat institution Yakesma Medan. object research used _ is Application of PSAK 109 concerning zakat accounting . Infaq / alms . Data analysis technique used done descriptive qualitative . Research results that application accounting requirements required by PSAK No.109 include recognition , measurement , presentation , and disclosure . In matter confession measurement , and presentation of LAZNAS Yakesma Medan has apply in accordance with PSAK NO.109, meanwhile in matter disclosure of LAZNAS Yakesma Medan not yet disclose completely.